The behavior of the hydrophobic effect under pressure and protein denaturation - Grigera, José Raúl (2010)
It is well known that proteins denature under high pressure. The mechanism that underlies such a process is still not clearly understood, however, giving way to controversial interpretations. Using molecular dynamics simulation on systems that may be regarded experimentally as limiting examples of the effect of high pressure on globular proteins, such as lysozyme and apomyoglobin, we have effectively reproduced such similarities and differences in behavior as are interpreted from experiment. From the analysis of such data, we explain the experimental evidence at hand through the effect of pressure on the change of water structure, and hence the weakening of the hydrophobic effect that is known to be the main driving force in protein folding.